Polarization Division Multiplexing of OFDM Radio-over-Fiber Signals in Passive Optical Networks. (27th February 2014) - Morant, Maria; Pérez, Joaquin; Llorente, Roberto
Abstract : This paper describes the state-of-the-art of polarization multiplexing for optical networks transmission. The use of polarization division multiplexing (PDM) permits to multiply the user capacity and increase the spectral efficiency. Combining PDM and orthogonal frequency division multiplexed (OFDM) modulation allows maximizing the optical transmission capacity. The experimental demonstration of transmitting OFDM signals following ECMA-368 ultrawide band (UWB) standard in radio-over-fiber using PDM in passive optical networks is herein reported. The impact of cross-polarization and cochannel crosstalk is evaluated experimentally in a three-user OFDM-UWB subcarrier multiplexed (SCM) configuration per polarization. Each SCM uses up to three OFDM-UWB channels of 200 Mbit/s each, achieving an aggregated bitrate of 1.2 Gbit/s with 0.76 bit/s/Hz spectral efficiency when using PDM transmission. The experimental results for the polarization-multiplexed SCM indicate that a 4 dB additional polarization crosstalk interference can be expected compared to a nonpolarization-multiplexed transmission system which translates to 2.4 dB EVM penalty in the UWB signals. The successful PDM transmission of SCM multiuser OFDM-UWB over a passive optical network of 25 km standard-single mode fiber (SSMF) reach is demonstrated.